Research status of community detection based on local expansion - Yancui SHI; Yuan WANG; Qing ZHAO; Xiankun ZHANG (Tongxin xuebao)
Community detection can effectively mine the characteristics of the network as well as the hidden information.Local expansion is a commonly used method of community detection,and it can be divided into two steps:the selection of seeds and the local expansion.Therefore,in order to analyze the advantages and disadvantages of the existing methods and their application,these methods about the selection of seeds,local expansion and evaluation were summarized,compared and analyzed.Then,the application and the research difficulties of community detection based on local extension were summarized.Finally,the research directions of community detection based on local expansion were given.